Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan pada Jasa Wisata (Open Trip) C.V Tidung Island - Muhammad Heykal; Sandy Prasetya; Pradnya Sari Harsanti (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2024)
The aim of this research is to determine the influence and identify the factors that have the greatest impact on the quality of service provided to Open Trip Tidung Island customers. The method in this research uses quantitative methods. Sampling in this study used accidental sampling. It was obtained that 41 respondents filled out questionnaires in observing Tidung Island using Open Trip Tidung_Island on 3-4 August 2024. Data analysis in this research uses simple linear regression analysis, coefficient of determination and correlation. Data obtained from the questionnaire is used to find the factors that most influence customer satisfaction in service quality. The Service Quality variable (X) has a significant effect on the Customer Satisfaction variable (Y), this is shown from the results of the Pearson Product Moment correlation analysis of 0.718 and includes a